Prevention of Rabies by Application of Lytta vesicatoria in Persian Medicine Texts in Islamic Civilization - Mostafa Moallemi; Mohammad Yousofpour; Assie Jokar (Tehran University of Medical Sciences, 2021)
Rabies is one of the most lethal diseases in human history. From the past, various drugs have been used to prevent the contraction of the disease when being bitten by a rabid animal. An insect called Ḏarārīḥ (Lytta vesicatoria), although poisonous, has in some cases been medically used. Greeks and Romans have used venomousness of this insect to treat skin diseases, but it has not been used to prevent rabies. This is a summative qualitative content analysis that focused on Persian Medicine (PM) texts from 2th to 13th AH centuries. Literature was searched during centuries 4th to 13th AH, by using this key words: ذراریح (Ḏarārīḥ), قنثاریدس (Cantharis/cantharides), and ئشفث Lytta vesicatoria and after extracting the data and analyzing them, the results were presented. In TPM texts, this insect was used to prevent rabies. This study has shown that the use of ḏarārīḥ (Lytta vesicatoria) in the prevention of rabies has been one of the innovations of the practitioners of Islamic civilization. The innovation proves that scholars in the period of Islamic civilization were not merely consumers or custodians of Roman, Greek, Indian, and Iranian knowledge, but added to it while preserving that knowledge.